Investment and profitability factors in mutual fund performance evaluation: a conditional approach - Leite, Paulo (2019)
This paper provides new evidence on the appropriateness of the Fama-French five-factor model to evaluate international equity funds’ performance. After extending this model to a conditional framework by allowing for time-varying risk and performance, the results show that funds underperformed during the 2000–2017 period. Funds investing globally and in Europe tend to invest in aggressive firms, but only the latter are exposed to firms with weak profitability. We thus conclude that although both investment and profitability factors are significant in explaining fund returns, the investment factor plays a more relevant role irrespective of the funds’ geographical area of investment.